Linking process and structure in the friction stir scribe joining of dissimilar materials: A computational approach with experimental support. (April 2018) - Gupta, Varun; Upadhyay, Piyush; Fifield, Leonard S.; Roosendaal, Timothy; Sun, Xin; Nelaturu, Phalgun; Carlson, Blair
Abstract: Friction stir welding (FSW) is a popular technique to join dissimilar materials in numerous applications. The solid state nature of the process enables joining materials with strikingly different physical properties. For welds in lap configuration, an enhancement to this technology is made by introducing a short, hard insert, referred to as a cutting-scribe, at the bottom of the tool pin. The cutting-scribe induces deformation in the bottom plate which leads to the formation of mechanical interlocks or hook like structures at the interface of two materials. A thermo-mechanical computational model employing a coupled Eulerian-Lagrangian approach is developed to quantitatively capture the morphology of these interlocks during the FSW process. Simulations using this model are validated by experimental observations. The identified interface morphology coupled with the predicted temperature field from this process–structure model can be used to estimate the post-weld microstructure and joint strength.